Photonic controlled metasurface for intelligent antenna beam steering applications including 6G mobile communication systems - Muqdad, Zainab S.; Alibakhshikenari, Mohammad; Elwi, Taha A.; Hassain, Zaid A. Abdul; Virdee, Bal. S.; Sharma, Richa; Khan, Salahuddin; Tokan, Nurhan Turker; Livreri, Patrizia; Falcone, Francisco; Limiti, Ernesto (ELSEVIER GMBH, 2023)
This paper presents a novel metasurface antenna whose radiation characteristics can be remotely controlled by optical means using PIN photodiodes. The proposed reconfigurable antenna is implemented using a single radiating element to minimize the size and complexity. The antenna is shown to exhibit a large impedance bandwidth and is capable of radiating energy in a specified direction. The proposed antenna consists of a standard rectangular patch on which is embedded an H-tree shaped fractal slot of order 3. The fractal slot is used to effectively reduce the physical size of the patch by 75 % and to enhance its impedance bandwidth. A metasurface layer is strategically placed above the patch radiator with a narrow air gap between the two. The metasurface layer is a lattice pattern of square framed rhombus ring shaped unit-cells that are interconnected by PIN photodiodes. The metasurface layer essentially acts like a superstrate when exposed to RF/microwave radiation. Placed below the patch antenna is a conductive layer that acts like a reflector to enhance the front-toback ratio by blocking radiation from the backside of the patch radiator. The patch's main beam can be precisely controlled by photonically illuminating the metasurface layer. The antenna's performance was modelled and analyzed with a commercial 3D electromagnetic solver. The antenna was fabricated on a standard dielectric substrate FR4 and has dimensions of 0.778 lambda(o) x 0.778 lambda(o) x 0.25 lambda(o) mm(3), where lambda(o) is the wavelength of free space centered at 1.35 GHz. Measured results confirm the antenna's performance. The antenna exhibits a wide fractional band of 55.5 % from 0.978 to 1.73 GHz for reflection-coefficient (S-11) better than -10 dB. It has a maximum gain of 9 dBi at 1.35 GHz with a maximum front-to-back ratio (F/B) of 21 dBi. The main beam can be steered in the elevation plane from -24 degrees to +24 degrees. The advantage of the proposed antenna is it does not require any mechanical movements or complicated electronic systems.
Keywords: Reconfigurable devices; Metasurface; Photonic systems; Fractal geometries; Patch antenna; Beam steering; DESIGN; Engineering; Telecommunications